Research of Management and Supervision: analysis in Counseling - Ahiruddin Ahiruddin (Journal of Leadership, Organization, Vision, and Administration, 2025)
Counseling services are an essential component of educational institutions in supporting students’ personal, social, academic, and career development. The effectiveness of these services is strongly influenced by the quality of school management and supervision, particularly the managerial competence of school principals as administrators, supervisors, and decision-makers. This study aims to analyze the implementation of management and supervision in counseling services by examining the processes of planning, organizing, actuating, and controlling, as well as their influence on counselor performance and program accountability. Using a library research method, the study reviews scientific books, journal articles, and relevant academic documents to synthesize concepts, theories, and empirical findings related to educational management, supervisory practices, and guidance and counseling program implementation. The results show that management and supervision significantly shape the quality of counseling programs, where weaknesses in planning, coordination, monitoring, and documentation contribute to the low effectiveness of guidance services in schools.